Enhancing methylene blue degradation via Mn, Co, and Al doped organic-ligand-stabilized ZnO nanoparticles: Experimental and DFT insights - Imran Ullah; Reinhard B Neder; Muhammad Irfan khan; Suriati Sufian; Huma Parwaz (Results in Physics, 2025)
Organic dyes contaminate a huge amount of water annually, resulting in potential risks for aquatic ecosystems. The removal of such contamination is addressed in this study by synthesizing highly stabilized manganese (Mn), cobalt (Co), and aluminum (Al)-doped zinc oxide (ZnO) ultra-small (US) nanoparticles (NPs) via the sol–gel approach and characterized through various characterization techniques. XRD confirmed single-phase crystallization in all samples, with crystallite/nanoparticle sizes ranging from 3 nm to 10 nm. A broad absorbance peak in the UV–Vis spectra signified size distribution, with the bandgap ranging from 3.02 to 3.06 eV for ZnO and reduced to 2.98 eV upon Co-doping. Density Functional Theory (DFT) calculations revealed improved structural and mechanical stability upon Co-doping and citrate (cit) capping. Furthermore, Co-doping and cit-capping improved the chemical reactivity of ZnO NPs. The cit-decorated 3 % Mn-doped ZnO photocatalyst improved the degradation efficiency from 27.02 mg/g to 29.63 mg/g. The 5 % Co-doped ZnO photocatalyst (cit-capped) exhibited 8.50 % higher dye degradation compared to ZnO-cit. Among dmlt-capped photocatalysts (ZnO), 5 % Al-doped remain an excellent photocatalyst and degrade 95.49 % dye in 180 min. DFT study revealed that cit-capping and Co-doping improve the light absorption of the photocatalysts, with an onset shift from 0.75 eV (ZnO) to 0.10 eV (ZnO cit). Co-incorporation into the ZnO lattice introduces an additional absorption peak in the visible range. Moreover, cit-capping also broadens the absorption range. Degradation kinetics of MB dye follow pseudo-first-order kinetics with R-squared values ranging from 0.90 to 0.99. Further improvements are possible through optimization of dopant levels (%), dye concentration, pH, and temperature.